Optimasi Peningkatan Karakteristik Crude Palm Oil (CPO) sebagai Bahan Bakar Diesel - Arifin, Ahmad Zaenal; Fadhilah, Rahadyan Itsar; Saputro, Erwan Adi (Universitas Batanghari Jambi, 2024)
Indonesia is one of the largest palm oil-producing countries in the world, significantly contributing to global palm oil needs. The use of palm oil as fuel is generally achieved through the biodiesel manufacturing process; however, this process remains costly and thus less economical. Additionally, the primary obstacle in using crude palm oil (CPO) is its high viscosity, which can cause blockages in the fuel injector channels of diesel engines. Therefore, modifications are necessary to enhance the characteristics of CPO so that it can be used directly as diesel engine fuel. This can be achieved through heating and the addition of 2-EHN additives. This study aimed to optimize the characteristics of CPO using Response Surface Methodology (RSM) to determine the optimal combination of temperature and 2-EHN concentration. The optimal point was identified at a temperature of 50°C and a 2-EHN concentration of 2%. The results of the CPO characteristic test showed a viscosity of 4.45 CSt, a density of 0.884 g/ml, a cetane number of 56.9, and a calorific value of 9314 kcal/kg